Findbuch der Bestände Abt. 57 bis Abt. 62: Preußisch-österreichische Übergangsbehörden 1863-1868/Abt. 57: Bundeskommissare für die Herzogtümer Holstein und Lauenburg 1863-1864; Abt. 58.1: Österreichisch-preußische Oberste Zivilbehörde für das Herzogtum Schleswig 1864; Abt. 58.2: Österreichisch-preußische Oberste Zivilbehörde für die Herzogtümer Schleswig, Holstein und Lauenburg 1864-1865; Abt. 59. - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2012)
After the end of the Schleswig-Holstein uprising, the European powers restored the Danish state to which the dukedoms of Schleswig, Holstein and Lauenburg belonged in 1851/1852. Denmark declared its decision not to join the Duchy of Schleswig.In 1863, however, the Danish government drafted a new constitution, which resulted in a link between the Duchy of Schleswig and Denmark and a separation from the Duchy of Holstein. The German Confederation (Deutscher Bund) considered this constitution to be a violation of the international agreements. When the new Danish king Christian IX (ruled 1863-1906) signed the constitution in the same year, Holstein and Lauenburg were occupied by federal contingents after Danish troops moved out. Until the establishment of the Prussian government in Schleswig in 1868, both parts of the country were administered by Prussian and Austrian transitional authorities.The provisional nature of these administrations and their authorities which usually operate for only a few months is also reflected in the complex inventory formation. In 2007, the holdings of the Prussian and Austrian administrations were reclassified. The processing also gave rise to an inventory adjustment. The signatures of the individual departments have been retained; only those with the addition of letters received a new number, which is also recorded in a concordance.A common register of places, subjects and persons for all collections forms the conclusion of this find book. To search for a topic or a term, the subject should first be classified according to subject and then added to the index.